Fast-FISH Detection and Semi-Automated Image Analysis of Numerical Chromosome Aberrations in Hematological Malignancies. (1998) - Esa, Arif; Trakhtenbrot, Luba; Hausmann, Michael; Rauch, Joachim; Brok-Simoni, Frida; Rechavi, Gideon; Ben-Bassat, Isaac; Cremer, Christoph
Abstract : A new fluorescence in situ hybridization (FISH) technique called Fast -FISH in combination with semi-automated image analysis was applied to detect numerical aberrations of chromosomes 8 and 12 in interphase nuclei of peripheral blood lymphocytes and bone marrow cells from patients with acute myelogenous leukemia (AML) and chronic lymphocytic leukemia (CLL). Commercially available α-satellite DNA probes specific for the centromere regions of chromosome 8 and chromosome 12, respectively, were used. After application of the Fast -FISH protocol, the microscopic images of the fluorescence-labelled cell nuclei were recorded by the true color CCD camera Kappa CF 15 MC and evaluated quantitatively by computer analysis on a PC. These results were compared to results obtained from the same type of specimens using the same analysis system but with a standard FISH protocol. In addition, automated spot counting after both FISH techniques was compared to visual spot counting after standard FISH. A total number of about 3, 000 cell nuclei was evaluated. For quantitative brightness parameters, a good correlation between standard FISH labelling and Fast -FISH was found. Automated spot counting after Fast -FISH coincided within a few percent to automated and visual spot counting after standard FISH. The examples shown indicate the reliability and reproducibility of Fast -FISH and its potential for automatized interphase cell diagnostics of numerical chromosome aberrations. Since the Fast -FISH technique requires a hybridization time as low as 1/20 of established standard FISH techniques, omitting most of the time consuming working steps in the protocol, it may contribute considerably to clinical diagnostics. This may especially be interesting in cases where an accurate result is required within a few hours.